Faktor–Faktor yang Mempengaruhi Minat Konsumen Membeli Mobil Toyota Avanza pada PT. Hadji Kalla Cabang Alauddin di Kota Makassar - Ramli, Ramli (Patria Artha University, 2017)
ABSTRACT Analysis of the factors that affect the interest of consumers to buy a car Toyota Avanza. This study aimed to determine the effect of the marketing mix that includes product, price, distribution, and promotion of the interests of consumers buy the Toyota Avanza. The sample used in this study are Toyota Avanza car user community of 100 people by questionnaire. This research is ex-post that are correlational, population and sample in this research is data questionnaire/ questionnaire containing questions related to consumer interest in buying a Toyota Avanza, given the numbers weighted by assessment strongly agree, agree, undecided, less agree and disagree with 100 respondents. Data were analyzed using correlation analysis and simple linear regression with the aid of a computer program SPSS 17.0 The research method using Multiple Regression Analysis, berdasarkankan data analysis and hypothesis testing with real level α = 0.05 this study shows that the F test results with a value of 33.034 with significant value is 0.000 indicates that the variable that consisted of Product, Price, Distribution and Promotion simultaneous positive influence on consumer interest to buy a car Toyota avanza at. Alauddin Branch Hadji Kalla in Makassar. The results of the t test for variables significant products 2.494 0.014 tcount, variable price significantly tcount 2.686 0.009, variable distribution of significant tcount 0,045 2,032 Promotion and variable tcount significant 5.656 0.000 partially shows a positive influence on consumer interest to buy a car Toyota Avanza. Results determinant coefficient (R2) was 0.763 meaning that Product, Pricing, Distribution and Promotion as independent variables are able to explain Interests Consumers are buying cars Toyota Avanza. Dependent Variables by 58.2% and has a strong and positive relationship, while the remaining 41.8% is the influence of other factors not included in the research model. Keywords: Product; price; distribution; and promotion.